Study on Plot Pattern and Farm Power Utilization for Major Crops in two Agro-climatic Zones of Hill Agriculture - Vasta, D K; Saraswat, D C (Journal of Agricultural Engineering, 2007)
A study was conducted in two major agro-climatic zones of Himachal Pradesh, namely Sub-montaneous Low Hills Sub-tropical (Zone-I) and Mid Hills Sub-humid (zone-II), to know the plot pattern and power utilization for major crops i.e. maize, paddy and wheat in hill farming. Average percentage of plots was 9.1, 14.8, 20.5, 25.3 and 30.3 in zone-I and 32.5, 26.4, 19.4, 14.2 and 7.6 in zone-II for the size less than 100, 100-200, 200-300, 300-400 and more than 400 mÂ², respectively. The vertical interval was observed to be 40-50 % higher in zone-II as compared to zone-I. The average plot width was 7.7, 10.5, 14.2, 16.8 and 25.3 min zone-I and 4.7, 8.6, 10.6, 13.4 and 20.5 m in zone-II with the plot size as stated above, which was 10-15% higher in zone-I as compared to zone-II. The shape of plots was 69 and 87% irregular and 31 and 13% regular with fragmented holding in zone-I and II, respectively. Overall animate power (481-619 man-h/ha and 104-138 animal-h/ha) was the major source of power for all the crops under different farm groups in the region. Source wise power utilization per unit area for major crops was 12-22, 10-12 and 5-14% higher in case ofman, animal and tractor, respectively in zone-II as compared to zone-I. Overall tractor power utilization was 2.5-17.3 h/ha (65.0-451.9 kWh/ha) and 2.0-20.20 h/ha (54.6-527.4 kWh/ha) for zone-I and zone-II, respectively with maximum in wheat and minimum in paddy crop. Tractor was not utilized by the farmers of zone-II for puddling due to small sized plots.